2014
DOI: 10.1371/journal.pone.0101973
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion Treatment for Knee Osteoarthritis: A Multi-Centre, Non-Blinded, Randomised Controlled Trial on the Effectiveness and Safety of the Moxibustion Treatment versus Usual Care in Knee Osteoarthritis Patients

Abstract: IntroductionThis study tested the effectiveness of moxibustion on pain and function in chronic knee osteoarthritis (KOA) and evaluated safety.MethodsA multi-centre, non-blinded, parallel-group, randomised controlled trial compared moxibustion with usual care (UC) in KOA. 212 South Korean patients aged 40–70 were recruited from 2011–12, stratified by mild (Kellgren/Lawrence scale grades 0/1) and moderate-severe KOA (grades 2/3/4), and randomly allocated to moxibustion or UC for four weeks. Moxibustion involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 26 publications
(30 reference statements)
2
90
0
Order By: Relevance
“…12,26 However, the adverse effects of moxa smoke restrict the development of traditional moxibustion. 27,28 In recent years, our group has developed a 10.6 lm laser moxibustion apparatus. The infrared radiation spectrum of traditional indirect moxibustion and human acupoints are very similar, and their radiation peaks are about 10 lm, which may produce resonance, playing a therapeutic role.…”
Section: Discussionmentioning
confidence: 99%
“…12,26 However, the adverse effects of moxa smoke restrict the development of traditional moxibustion. 27,28 In recent years, our group has developed a 10.6 lm laser moxibustion apparatus. The infrared radiation spectrum of traditional indirect moxibustion and human acupoints are very similar, and their radiation peaks are about 10 lm, which may produce resonance, playing a therapeutic role.…”
Section: Discussionmentioning
confidence: 99%
“…One RCT 21 revealed that the participants with moxibustion experienced a considerably significant improvement in a GH score than the control group at week 6 ( P  = 0.015) and week 12 ( P  = 0.029); the same result applied to the VT score at week 12 ( P  = 0.042). The other study 23 reported that the BP score, PF score, or SF score in the patients with moxibustion were separately higher than those scores of the patients in the control group ( P  = 0.0003 at week 5, 13; P  = 0.0025 at week 5; and P  = 0.0418 at week 5). The data in all of the subcategories of the SF-36 scale were quantitatively synthesized in the meta-analysis.…”
Section: Resultsmentioning
confidence: 79%
“…Otherwise, 3 RCTs 20,21,23 noted region adverse reactions, for example, blisters, burn wounds, and skin flushing in local lesions. Two studies 21,23 reported systemic AEs; however, only 1 23 reported positive symptoms, that is, pruritus and fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…Sample size was estimated as described previously [19], which considered a change in the population mean on the numerical rating scale (NRS) for each group (1, EM group; 2, TIM group; 3, usual care group). The null and alternative hypotheses are:…”
Section: Methodsmentioning
confidence: 99%
“…Treatments will be provided bilaterally in participants with pain in both knees. The treatment acupoints were selected based on a consensus of doctors of traditional Korean medicine, a text book, literature reviews, and additional studies [10, 19, 20]. The participants will be asked to wear loose clothing for easy exposure of the knee joints, and to maintain a comfortable supine position during treatment.
Fig.
…”
Section: Methodsmentioning
confidence: 99%